Evaluating Manual Palpation Trajectory Patterns in Tele-manipulation for Soft Tissue Examination - Konstantinova, Jelizaveta; Min Li; Aminzadeh, Vahid; Althoefer, Kaspar; Nanayakkara, Thrishantha; Dasgupta, Prokar (2013 IEEE International Conference on Systems, Man, and Cybernetics, 2013)
Robot-assisted minimal invasive surgery made it possible to improve the quality of surgical procedures and to enhance clinical outcomes. However, the need to palpate soft tissue organs with the aim to localize potential sites of abnormalities in real time has been recognized. For this work, ten subjects were recruited to perform a remote palpation procedure on a silicone phantom utilizing a tele-manipulation setup, to study their behavior when remotely palpating soft tissue. The stiffness values acquired during the remote palpation of a silicone phantom were transferred to the subjects by means of haptic and visual feedback. Participating subjects were asked to detect hard nodules in the silicone tissue using two distinct strategies: a) randomly chosen movements, and b) trajectory pattern, based on manual palpation techniques for clinical breast examination. We have compared relevant parameters, defining patterns observed during manual palpation, with the counterpart patterns occurring during remote palpation. The results show the effectiveness of applying palpation trajectory pattern used during manual soft tissue examination to tele-manipulation palpation.